A review on the role of allylic and bis allylic positions in biodiesel fuel stability from reported lipid sources. Issue 5 (3rd September 2017) - Iyer, Ramasubramania
ABSTRACT: Reported procedures of estimating allylic position equivalent (APE), bis allylic position equivalent (BAPE) and oxidizability is applied to reported work on autoxidation of methyl oleate with addition of methyl linoleate at 20 and 50 °C. Plot of reported peroxide value (PV) versus estimated oxidizability of autoxidation reactions indicates the effect of APE in rapidly increasing PV of neat methyl oleate at 50 °C. Plot of estimated oxidizablity versus estimated APE and BAPE of reported unsaturated fatty acid methyl esters (FAME) from four lipid sources results in novel insights of a linear relationship of oxidizability with BAPE and non-linear relationship with APE. Limitations of iodine value (IV) as an oxidation stability standard for biodiesel is highlighted by comparing with reported oxidation stability measurements of FAME from two lipid sources. Comments on thermal stability of biodiesel and antioxidants reveals challenges of preparing robust rugged antioxidants for oxidative as well as thermal stability.